THE TEACHING OF LITERATURE ACCORDING TO ANTONIO CANDIDO - Antunes, Benedito [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2019)
Professor Antonio Candido (1918-2017) was, as a few people in Brazil were, a confirmed humanist, who applied his principles to everything he had done as a professor, thinker and political activist. Strictly speaking, all such facets of his were marked by his role as a professor, concerned about fostering education for life within society. Based on the study of texts broaching Brazilian literary theory and literature, this paper was carried out to outline the conception of literature teaching in Antonio Candido's work, in order to contribute to the reflection on literary reading in classroom at a level which goes beyond merely didactic considerations and deals with literature as a relevant factor for human background development nowadays.
Keywords: teaching of literature; Antonio Candido; Brazilian literature; literary reader's; background development